Primordial Helium‐3 Exchange Between Earth's Core and Mantle - Peter L. Olson; Zachary D. Sharp (Geochemistry, Geophysics, Geosystems, 2022)
Abstract Volatiles from the solar nebula are known to be present in Earth's deep mantle. The core also may contain solar nebula‐derived volatiles, but in unknown amounts. Here we use calculations of volatile ingassing and degassing to estimate the abundance of primordial 3He now in the core and track the rate of 3He exchange between the core and mantle through Earth history. We apply an ingassing model that includes a silicate magma ocean and an iron‐rich proto‐core coupled to a nebular atmosphere of solar composition to calculate the amounts of 3He acquired by the mantle and core during accretion and core formation. Using experimentally determined partitioning between core‐forming metals and silicate magma, we find that dissolution from the nebular atmosphere deposits one or more petagrams of 3He into the proto‐core. Following accretion, 3He exchange depends on the convective history of the coupled core‐mantle system. We combine determinations of the present‐day surface 3He flux with estimates of the present‐day mantle 3He abundance, mantle and core heat fluxes, and our ingassed 3He abundances in a convective degassing model. According to this model, the mantle 3He abundance is evolving toward a statistical steady state, in which surface losses are compensated by enrichments from the core.